ASSOCIATIONS BETWEEN INDIVIDUAL RETINAL LAYER THICKNESSES AND DIABETIC PERIPHERAL NEUROPATHY USING RETINAL LAYER SEGMENTATION ANALYSIS. Issue 11 (November 2018) - Kim, Jin Hyung; Lee, Min Woo; Byeon, Suk Ho; Kim, Sung Soo; Koh, Hyoung Jun; Lee, Sung Chul; Kim, Min
Abstract : Purpose: To evaluate clinical correlations between the thicknesses of individual retinal layers in the foveal area of diabetic patients and the presence of diabetic peripheral neuropathy (DPN). Methods: This retrospective, observational, cross-sectional study enrolled a total of 120 eyes from 120 patients. The eyes were divided into 3 groups: normal controls (n = 42 eyes), patients with diabetes mellitus (n = 42 eyes) but no DPN, and patients with diabetes mellitus and DPN (n = 36 eyes). The primary outcome measures were the thickness of all retinal layers in the central 1-mm zone measured using the segmentation analysis of spectral-domain optical coherence tomography. Correlations between the thicknesses of the individual retinal layers and the presence of DPN were also analyzed. Logistic regression analyses were used to determine which change in layer thickness had the most significant association with the presence of DPN. Results: The mean thicknesses and the ratios of retinal nerve fiber layers to total retina thicknesses in the DPN group were 10.77 ± 1.79 μ m and 4.10 ± 0.55%, which was significantly lower than those in normal controls and the diabetes mellitus with no DPN group ( P = 0.014 and P = 0.001, respectively). Logistic regression analyses also showed that the decrease in thicknesses of the retinal nerve fiber layers and the inner nuclear layer are significant factors for predicting a higher risk for DPN development (odds ratio = 7.407 and 1.757; P < 0.001 and P = 0.001, respectively). Conclusion: A decrease in the retinal nerve fiber layer and the inner nuclear layer thickness was significantly associated with the presence of DPN. Abstract : The thinning of retinal nerve fiber layer in macula of diabetic patients was found to have significant association with the development of diabetic peripheral neuropathy using retinal layer segmentation analysis of spectral-domain optical coherence tomography.